Potentially Inadequate Medications in the Elderly: PRISCUS 2.0 - Mann, Nina-Kristin; Mathes, Tim; Sönnichsen, Andreas; Pieper, Dawid; Klager, Elisabeth; Moussa, Mahmoud; Thürmann, Petra A (Deutsches Ärzteblatt international, 2023)
The term potentially inadequate medication (PIM) is used to describe substances that may be unsuitable for use inthe elderly and should be avoided. The PRISCUS list, published in 2010, was the first catalog of PIM designed for the Germandrug market to become adopted in practice. While 24% of German patients aged ≥ 65 years were prescribed at least one PIMper year in 2009, the proportion in 2019 was only 14.5%.BACKGROUNDThe term potentially inadequate medication (PIM) is used to describe substances that may be unsuitable for use inthe elderly and should be avoided. The PRISCUS list, published in 2010, was the first catalog of PIM designed for the Germandrug market to become adopted in practice. While 24% of German patients aged ≥ 65 years were prescribed at least one PIMper year in 2009, the proportion in 2019 was only 14.5%.In a three-round Delphi process, experts from clinical practice and research evaluated whether selected substancesare PIM for the elderly. The participants were provided with dedicated literature including systematic reviews carried out for theparticular purposes of this project.METHODSIn a three-round Delphi process, experts from clinical practice and research evaluated whether selected substancesare PIM for the elderly. The participants were provided with dedicated literature including systematic reviews carried out for theparticular purposes of this project.Fifty-nine persons took part in the Delphi process and, in addition, contributed comments and therapeutic alternatives.Altogether, 187 substances were classed as PIM. One hundred thirty-three of the substances now listed were not in the originalPRISCUS list: these include some oral antidiabetics, all of the selective COX-2 inhibitors, and moderately long acting benzodiazepinessuch as oxazepam. For some other substances, e.g., proton pump inhibitors (PPI), the advisability of treatment formore than 8 weeks was considered as potentially inappropriate, as was the use of ibuprofen in doses >1200 mg/day and formore than 1 week without PPI. Risperidone for more than 6 weeks is also PIM.RESULTSFifty-nine persons took part in the Delphi process and, in addition, contributed comments and therapeutic alternatives.Altogether, 187 substances were classed as PIM. One hundred thirty-three of the substances now listed were not in the originalPRISCUS list: these include some oral antidiabetics, all of the selective COX-2 inhibitors, and moderately long acting benzodiazepinessuch as oxazepam. For some other substances, e.g., proton pump inhibitors (PPI), the advisability of treatment formore than 8 weeks was considered as potentially inappropriate, as was the use of ibuprofen in doses >1200 mg/day and formore than 1 week without PPI. Risperidone for more than 6 weeks is also PIM.The new, greatly extended PRISCUS list must now be validated in epidemiological and prospective studies and itspracticability in routine daily use must be verified.CONCLUSIONThe new, greatly extended PRISCUS list must now be validated in epidemiological and prospective studies and itspracticability in routine daily use must be verified.